2014
DOI: 10.1111/bjd.12787
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of inverse recurrent suppuration: a population-based study of possible hidradenitis suppurativa

Abstract: Data on IRS suggest that HS may be more prevalent than previously suggested, and the prevalence may be comparable to other major dermatoses, e.g. psoriasis. However, as no physician examination was done, the risk of recall and information bias is a major limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
170
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(183 citation statements)
references
References 24 publications
5
170
1
7
Order By: Relevance
“…HS has been considered to be a rare disorder but European studies based on population samples using validated questionnaires have suggested a prevalence of 1%-2% in the general population and a peak prevalence of 4% (including mild cases) among young adults [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…HS has been considered to be a rare disorder but European studies based on population samples using validated questionnaires have suggested a prevalence of 1%-2% in the general population and a peak prevalence of 4% (including mild cases) among young adults [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, most experts concur that the maximum duration of the active form of HS in a given patient is about 20 years [6]. With regard to the estimated prevalence of the disease in European countries and in the United States, available data differ by up to four orders of magnitude, ranging from 0.00033% to 4.1% [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Situation In the Usa And Europementioning
confidence: 99%
“…Więk-szość ekspertów jest również zgodna, że czas trwania czynnej postaci HS wynosi u danego pacjenta maksymalnie ok. 20 lat [6]. Dane dotyczące częstości wystę-powania choroby w krajach europejskich i USA różnią się nawet o 4 rzędy wielkości i mieszczą się w przedziale od 0,00033% do 4,1% [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Sytuacja W Usa I Europieunclassified
“…axilla, inguinal and anogenital areas [1]. Recent studies indicate a prevalence of 2.1% in the general population [2] and a rising incidence [3], making it a not uncommon skin disease.…”
Section: Introductionmentioning
confidence: 99%